The Legal Regime of Interest Rates in Peruvian Legislation: Usury Interest Rates Within and Outside the National Financial System Generated by Law No. 31143 - Castellares Aguilar, Rolando (2024)
Law No. 31143 has increased the Maximum Interest Rates to usury levels, especially for the sector outside the financial system; while operations within the financial system will no longer have interest rates freely determined by the parties, but rather some banking operations will be subject to Maximum Rates; while the other operations will have interest rates according to free supply and demand, thus generating a double regime for the operations of the financial system.On the other hand, the Maximum Interest Rates applicable to operations outside the financial system, such as the operations of the financial system subject to control, will have the same Maximum Rates, they will be determined semiannually; Therefore, these Maximum Rates will vary each semester, applying to the transactions agreed upon during that semester; all of which will generate complexity and conflicts between the parties.